DAMPAK PERSEMBAHAN SUKARELA BAGI JEMAAT MISKIN DI GPIBK JEMAAT KALVARI SABANG - Langido, Seprialince; Mosooli, Ermin Alperiana; Ruindungan, Leo Mardany (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2022)
Today some churches do not prescribe tithing but voluntary offerings. This study intends to conduct a study of churches that set voluntary offerings to find out: 1) whether the offerings given are lower or higher than one-tenth of income; 2) are the percentages the same for all levels in the church. The research subject is the Indonesian Protestant Church in Banggai Islands (GPIBK), one of the churches that do not apply tithing offerings. The research focuses on one of the largest congregations in GPIBK, the Kalvari Sabang Congregation, located in Sabang, North Bulagi sub-district, Banggai Islands district Central Sulawesi province. The method used is quantitative with a comparative study approach. A comparison of offerings is made based on social class, namely upper class, middle class, and lower class. The control variables are the total monthly income, the total monthly offerings to the church, and the percentage of the total monthly offerings to the church to the total monthly income. The unit of analysis is the family. The total number of families involved was 28 families. The study results are as follows: first, the Kalvari Sabang congregation gives offerings exceeding one-tenth of their income every month. The upper-class average is 12.52%, the middle class is 21.79%, and the lower class is 30.17%. Second, the percentage of offerings from the lower class is higher than that of the middle and upper classes. The lower the social class, the higher the percentage of giving to the church.